Therapeutic efficacy of clomiphene citrate combined with metformin in patients with polycystic ovary syndrome. (7th November 2021) - Lin, Wenxun; Feng, Jun; Zhou, Honggui; Chen, Xiaofen; Diao, Wei; Ma, Peng
Abstract: What is known and objective: Although several clinical trials have compared the clinical efficacy of clomiphene citrate (CC) combined with metformin (MET) in the treatment of women with polycystic ovary syndrome (PCOS), the results are controversial. Therefore, this study was designed to conduct a pooled analysis to evaluate the efficacy of CC combined with MET versus CC in these patients. Methods: Computerized searches of the PubMed, Web of Science, Embase and Cochrane Library databases were conducted to identify eligible randomized controlled trials (RCTs) from the data obtained up to June 2021. The Cochrane Collaboration risk of bias tool was used to assess the risk of bias in individual RCTs, and RevMan 5.4 was used for data statistical analysis. Results and discussion: A total of 13 RCTs were included in the meta‐analysis. These studies involved 1, 353 patients, 707 of these were in the combination group and 646 in the monotherapy group. The results indicated a higher clinical pregnancy rate (risk ratio [RR] 1.28, 95% confidence interval [CI] 1.06–1.54, p  = 0.01) in the combined group compared to the monotherapy group. However, no significant differences were observed in the ovulation rate (RR 1.13, 95% CI 0.98–1.30, p  = 0.10), live birth rate (RR 1.13, 95% CI 0.89–1.42, p  = 0.32), multiple pregnancy rate (RR 0.58, 95% CI 0.19–1.73, p  = 0.33) and abortion rate (RR 1.26, 95% CI 0.86–1.84, p  = 0.23) between the two groups. What is new and conclusion: CC combined with MET has an advantage in improving the clinical pregnancy rate compared to CC alone; however, there is no significant difference in the rate of ovulation. For better management of PCOS, a high‐quality RCT is needed to demonstrate the safety of the combination.